2018
DOI: 10.1093/schbul/sbx166
|View full text |Cite
|
Sign up to set email alerts
|

Can We Reduce the Duration of Untreated Psychosis? A Systematic Review and Meta-Analysis of Controlled Interventional Studies

Abstract: Reduction of duration of untreated psychosis (DUP) is the key strategy of early interventions for improving the outcomes of first-episode psychosis. Although several controlled interventional studies have been conducted with the aim of reducing DUP, the results are highly inconsistent and conflicting. The current study systematically searches Web of Science and Ovid for English original articles investigating interventions adopted to reduce DUP, compared to a control intervention, up to April 6, 2017. Sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 63 publications
1
95
0
3
Order By: Relevance
“…It is well known that the general public's stigma toward schizophrenia is significantly higher than other mental illnesses (Baba et al, 2017;Lee et al, 2016;Pescosolido et al, 2010;Schomerus et al, 2012), consequently, the stigma might result in delayed detection, prolonged duration of untreated psychosis (DUP), and further lead to poorer long-term symptomatic and functioning prognosis (Marshall et al, 2005;Penttilä, Jääskeläinen, Hirvonen, Isohanni, & Miettunen, 2014). Efforts focused on reduction of DUP alone might not be effective as a recent review concluded negative evidence on pooling results of available interventions for reducing DUP (Oliver et al, 2018). Jorm (2000) has proposed that mental health literacy, defined as "knowledge and beliefs about mental disorders which aid their recognition, management, or prevention," is a key notion for community mental health education if we hope to enhance early recognition.…”
Section: Stigma and Barrier To Treatment In Mental Illnessmentioning
confidence: 99%
“…It is well known that the general public's stigma toward schizophrenia is significantly higher than other mental illnesses (Baba et al, 2017;Lee et al, 2016;Pescosolido et al, 2010;Schomerus et al, 2012), consequently, the stigma might result in delayed detection, prolonged duration of untreated psychosis (DUP), and further lead to poorer long-term symptomatic and functioning prognosis (Marshall et al, 2005;Penttilä, Jääskeläinen, Hirvonen, Isohanni, & Miettunen, 2014). Efforts focused on reduction of DUP alone might not be effective as a recent review concluded negative evidence on pooling results of available interventions for reducing DUP (Oliver et al, 2018). Jorm (2000) has proposed that mental health literacy, defined as "knowledge and beliefs about mental disorders which aid their recognition, management, or prevention," is a key notion for community mental health education if we hope to enhance early recognition.…”
Section: Stigma and Barrier To Treatment In Mental Illnessmentioning
confidence: 99%
“…Although not all early intervention programs have been able to shorten DUP (Oliver et al 2018), the goal of reducing DUP is attainable as demonstrated by successful programs (e.g., Melle et al 2012). Over time, these programs coupled with efforts to improve antipsychotic adherence will generate sufficient numbers of treated individuals to enable empirical research of their long-term effects on clinical, functional, and economic outcomes.…”
Section: Implications For Researchmentioning
confidence: 99%
“…Recent evidence that "Clinical High Risk for Psychosis" (CHR-P) services may be beneficial in reducing the negative impact of Duration of Untreated Psychosis (DUP) on both direct and indirect costs of care (Oliver et al, 2018) also contributed to spread focused EIP protocols (most often as centralized and autonomous services) within the mental health care network of different countries .…”
Section: Introductionmentioning
confidence: 99%